Cytotoxic and natural killer cell stimulatory constituents of Phyllanthus songboiensis. (March 2015) - Ren, Yulin; Yuan, Chunhua; Deng, Youcai; Kanagasabai, Ragu; Ninh, Tran Ngoc; Tu, Vuong Tan; Chai, Hee-Byung; Soejarto, Djaja D.; Fuchs, James R.; Yalowich, Jack C.; Yu, Jianhua; Douglas Kinghorn, A.
Graphical abstract: Nine compounds, seven known, were isolated and identified from Phyllanthus songboiensis . An arylnaphthalene lignan was highly cytotoxic toward HT-29 cells, and a known phytosterol was found to stimulate natural killer cells in the presence of interleukin 12. Highlights: Nine compounds, seven known, were isolated from Phyllanthus songboiensis . Structures were determined by analysis of their spectroscopic data. The known arylnaphthalene lignan was highly cytotoxic toward HT-29 cells. The known arylnaphthalene lignan did not act as a DNA topoisomerase IIα poison. The known phytosterol stimulated NK cells in the presence of interleukin 12. Abstract: A dichapetalin-type triterpenoid and a dibenzylbutyrolactone-type lignan, together with five known lignans, a known aromatic diterpenoid, and a known acylated phytosterol, were isolated from the aerial parts of Phyllanthus songboiensis, collected in Vietnam. Their structures were determined by interpretation of the spectroscopic data, and the inhibitory activity toward HT-29 human colon cancer cells of all isolates was evaluated by a cytotoxicity assay. The known arylnaphthalene lignan, (+)-acutissimalignan A, was highly cytotoxic toward HT-29 cells, with an IC50 value of 19 nM, but this compound was inactive as a DNA topoisomerase IIα (topo IIα) poison. The known phytosterol, (−)-β-sitosterol-3- O -β-d -(6- O -palmitoyl)glucopyranoside, was found to stimulate natural killer (NK) cells at a concentration of 10 μM in the presence of interleukin 12 (IL-12).